Cross-talk of renal cells through WNT signal transduction in the development of fibrotic kidneys - Chen, Yuhong; Xue, Chao (Frontiers in Cell and Developmental Biology, 2025)
Chronic kidney disease (CKD) is a progressive condition that can lead to chronic renal failure (CRF), affecting 8%–16% of adults globally and imposing a significant burden on healthcare systems. Renal fibrosis is a key pathological hallmark of CKD progression and is linked to poor prognosis. Multiple signaling pathways, including WNT/β-catenin.Aberrant activation of WNT/β-catenin is implicated in renal fibrosis. The roles of renal macrophages and fibroblasts are pivotal in fibrosis progression and prognosis.